2020
DOI: 10.3390/ijerph17186702
|View full text |Cite
|
Sign up to set email alerts
|

Children in South Africa with and without Intellectual Disabilities’ Rating of Their Frequency of Participation in Everyday Activities

Abstract: In a low-and middle-income country (LMIC) such as South Africa, not much is known about how children with intellectual disabilities (ID) participate in everyday activities, as no studies to date have compared their participation to peers without ID from the same background. Using a newly developed, contextually valid measure of participation, Picture my Participation (PmP), 106 children with (73) and without ID (33), rated their frequency of participation in activities of daily living. Previous international r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 40 publications
5
12
3
Order By: Relevance
“…A comparative study demonstrated that children with disabilities from low-income families had disadvantages regarding social and community participation, access to health service and self-care compared with peers from high-income families. 10 Moreover, those results corroborated with our caregivers' complaints about the socioeconomic scenario, evidencing the need for complex dynamics for the care of Recent findings on the perception of parents and health professionals about the care of children with CZS showed positive aspects of patient-centred care, highlighting the quality of the SUS to meet the biopsychosocial demands of these children. 35 Early access to health care has positive effects on children with CZS.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…A comparative study demonstrated that children with disabilities from low-income families had disadvantages regarding social and community participation, access to health service and self-care compared with peers from high-income families. 10 Moreover, those results corroborated with our caregivers' complaints about the socioeconomic scenario, evidencing the need for complex dynamics for the care of Recent findings on the perception of parents and health professionals about the care of children with CZS showed positive aspects of patient-centred care, highlighting the quality of the SUS to meet the biopsychosocial demands of these children. 35 Early access to health care has positive effects on children with CZS.…”
Section: Discussionsupporting
confidence: 81%
“…35 Early access to health care has positive effects on children with CZS. 10 Our results also indicated that adequate access to health services and spatial accessibility in cities is essential for the routine organization of families with children with CZS. 34 The favourable disposition of health service (i.e., localization, spatial accessibility and transportation adequacy) for people with disabilities were a requirement for life planning of families, as observed in findings regarding the transition to adulthood of children with disabilities.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations